“Quel genere di macchine che possono esplodere”. Apocalissi della tecnica e integrazione della cultura - Pinto, Valeria (Mechane, 2025)
These essay takes its cue from Umberto Eco’s formula ‘Apocalyptic and Integrated’, which he proposed over half a century ago, highlighting its conceptual weakness despite its undoubted ideological effectiveness, and the thoroughly conservative idea of culture as ‘objective spirit’ (Hegel) that underlies it. Through Nietzsche and a genealogy of Heidegger’s critique of the concept of culture – from his early writings to The Age of the World Picture, the Black Notebooks and beyond – the technical-conservative nature of Kultur and cybernetics as its operational culmination is clarified. Furthermore, a reading of the central tenets of Gotthard Günther’s ‘metaphysics of cybernetics’ confirms the origin of cybernetics in Hegel’s doctrine of spirit. Finally, drawing on Reiner Schürmann’s insights, the anarchic nature of Heidegger’s critique of technical thought and its debt to Nietzschean criticism are emphasised.